Efficient suppression of parkinsonian beta oscillations in a closed-loop model of deep brain stimulation with amplitude modulation - Bahadori-Jahromi, Fatemeh; Salehi, Sina; Madadi Asl, Mojtaba; Valizadeh, Alireza (Frontiers in Human Neuroscience, 2023)
‎Parkinson's disease (PD) is a movement disorder characterized by pathological beta band (15-30 Hz) neural oscillations within the basal ganglia (BG)‎. ‎It is shown that the suppression of abnormal beta oscillations is correlated with the improvement of motor symptoms which is a goal of standard therapies including deep brain stimulation (DBS)‎. ‎To overcome the stimulation-induced side-effects and inefficiencies of conventional DBS (cDBS) and to reduce the administered stimulation current‎, ‎closed-loop adaptive DBS (aDBS) techniques were developed‎. ‎In this method‎, ‎frequency and/or amplitude of stimulation are modulated based on various disease biomarkers‎. ‎Here‎, ‎by computational modeling of a cortico-BG-thalamic network in normal and PD condition‎, ‎we show that closed-loop aDBS of subthalamic nucleus (STN) with amplitude modulation leads to a more effective suppression of pathological beta oscillations within the parkinsonian BG‎. ‎In this way‎, ‎beta band neural oscillations are restored to their normal range and the reliability of the response of the thalamic neurons to motor cortex commands is retained‎. ‎Furthermore‎, ‎notably less stimulation current is administered during aDBS compared to cDBS due to a closed-loop control of stimulation amplitude based on the STN local field potential (LFP) beta activity‎. ‎Such efficient models of closed-loop stimulation may contribute to the clinical development of optimized aDBS techniques to reduce potential stimulation-induced side-effects of cDBS in PD patients while leading to a better therapeutic outcome.